Stories of a Revolution, or "Un peuple qui se prépare à devenir nation" - Arvanitakis, Dimitris (Historein, 2025)
How do we study a Revolution? How does the study of the Greek Revolution fit into the wider frame of Revolutions? When does the study of the Greek Revolution answer to historiographical requests and when respond to ideological needs of the present? This text attempts to approach these issues, expressing some thoughts on three recent books on the Greek Revolution: Petros Pizanias, Η Ελληνική Επανάσταση, 1821–1830 [The Greek Revolution, 1821–1830]. Athens: Estia, 2021. 272 pp. Mark Mazower, Η Ελληνική επανάσταση [The Greek Revolution]. Athens: Alexandria, 2021. 566 pp. Originally published as The Greek Revolution: 1821 and the Making of Modern Europe. London: Allen Lane, 2021. 574 pp. Aristides Hatzis, Ο ενδοξότερος αγώνας: Η Ελληνική Επανάσταση του 1821 [The most glorious struggle: The Greek Revolution of 1821]. Athens: Papadopoulos, 2021. 640 pp.